Cover Picture: Development of Small‐Molecule Trypanosoma brucei N‐Myristoyltransferase Inhibitors: Discovery and Optimisation of a Novel Binding Mode (ChemMedChem 11/2015). Issue 11 (November 2015) - Spinks, Daniel; Smith, Victoria; Thompson, Stephen; Robinson, David A.; Luksch, Torsten; Smith, Alasdair; Torrie, Leah S.; McElroy, Stuart; Stojanovski, Laste; Norval, Suzanne; Collie, Iain T.; Hallyburton, Irene; et al.
Abstract : The front cover picture shows the enzyme N‐ myristoyltransferase from the pathogen Trypanosoma brucei . Next to this is an image of the parasite. Also shown are an inhibitor of the protein that we have previously reported (bottom structure) and two novel scaffolds (top structures) that are reported in our paper in this issue. More details can be found in the Full Paper by Ian H. Gilbert et al. onpage 1821 in Issue 11, 2015 (DOI:10.1002/cmdc.201500301 ).